Prevalence, risk factors and antifungal susceptibility pattern of Candida species among pregnant women at Debre Markos Referral Hospital, Northwest Ethiopia - Alem Tsega; Feleke Mekonnen (BMC, 2019)
Abstract Background Candida is the commonest opportunistic fungi in human. Candida species cause diverse types of diseases. Vaginal candidiasis has been reported as one of the most common type of fungal diseases among pregnant women. However; In Ethiopia, due to scarcity of data, much has not been documented regarding the prevalence of Candida among pregnant women. Objective This study aimed to determine the prevalence, possible risk factors and antifungal susceptibility profile of Candida species among pregnant women attending Debre Markos Referral Hospital, Northwest Ethiopia. Method A cross-sectional study was conducted from February to May 2017. A total of 384 pregnant women were included using a systematic random sampling technique. Vaginal specimens were collected, inoculated on Candida HiV eg culture Medium and incubated at 37 °C for 24 h.Colonies were identified using standard microbiological methods and selected for further Candida Species identification using Hi Chrome agar and germ tube test. Fungal suspensions were made and adjusted at 0.5% MacFarland standard. Modified Kirby-Bauer disk diffusion technique was used for antifungal susceptibility. Data was entered, cleaned using Ep info version 7.1and transported to Statistical Packages for Social Sciences (SPSS) version 21 for analysis. Descriptive statistics and logistic regression were performed. P. value < 0.05 at 95% confidence interval was considered as statistically significant. Result From a total of 384 study participants, 96 (25%) were positive for Candida species. The predominant Candida species was Candida albicans 54(56.25%) followed by Candida krusei 21(21.9%), Candida glabrata 17(17.7%), Candida tropicalis 1(1%) and 3(3.1%) were other Candida species. Contraceptive use (AOR: 0.394; 95% CI = 0.20-0.74) and prolonged antibiotic uses (AOR: 0.393; 95% CI = 0.21-0.72) were risk factors. All isolates except Candida krusei were 100% susceptible to amphotericin-B. Resistance rate was high against itraconazole and Ketoconazole 55(57.3%). Conclusion The prevalence of Candida species among symptomatic pregnant women was significantly higher than asymptomatic pregnant women. Age group between 26 and 40 years was significantly associated with Candida infection. Amphotericin B was the most sensitive antifungal drug. High rate of multiple drugs resistant Candida species was detected. Therefore Symptomatic women should be routinely screened and treated.